PKM PELATIHAN KEPEMIMPINAN DAN MANAJEMEN BAGI PENGURUS ORGANISASI SANTRI ISMAH : (Studi Kasus pada Organisasi Ikatan Santri Pondok Pesantren Badridduja Wilayah Al-Mashduqiah Kraksaan Probolinggo) - Muhammad Ainul Yaqin; Moh. Rifa’i; Fatimah Al Zahra; Moh. Rofiki; Eka Diana; Mukhlisin Saad; Ahmad Tijani; Malikul Habsy (Pusat Riset dan Inovasi Nasional, 2022)
The management of the Santri organization consisting of senior students at the Al-Mashduqiah Islamic Boarding School Kraksaan Probolinggo is a fairly important and potential human resource in leading the daily activities of all students at the Badridduja Islamic Boarding School in the Al-Mashduqiah Region. Its effectiveness and efficiency is highly dependent on the leadership of the ISMAH organization so that leadership and management training is very important for the administrators for self-development, training to become quality leaders and managers. This community service is carried out by implementing the PAR (Participatory Action Research) approach strengthened by field survey methods, analysis of problems developing in the field, FGD (Focus Group Discussion), SWOT analysis, direct action in the field consisting of mentoring programs in the preparation of organizational work programs. , assistance in the dynamics and sharing of organizational affairs, assistance in work evaluation activities, assistance in increasing the effectiveness of student discipline, and the implementation of a mini workshop program on leadership and management for organizational management. The results of this service contribute to controlling work program decisions that are not in accordance with the organization's SWOT analysis, Strengthening organizational HR work and increasing work understanding within the organization, Controlling irrelevant work programs and compiling feedback for further planning, Realizing a quality work culture that has implications for effectiveness and performance efficiency, and Improving the quality of understanding and understanding of organizational human resources theoretically and practically. This training is carried out by an organized team, by providing some materials and practices of leadership and management that have been planned for approximately 9 months. In addition, the team also accompanied the activities carried out in a planned manner by the management in order to monitor and evaluate the practices that needed to be improved so as to provide best practices for ISMAH administrators in carrying out their leadership and management tasks.